Strategi Guru Untuk Memotivasi Anak Dalam Kesulitan Belajar - Opi Andriani; Eni Patmala; Hikmawati Santesa; Zuli Nufiana (LPPM Politeknik Pratama, 2024)
The purpose of this research is to find out a description of teachers' strategies in motivating students to learn, to find out the supporting and inhibiting factors in motivating students to learn. This research is a descriptive study with a qualitative approach. Data collection techniques were carried out using observation, interviews and documentation. The results of the research show that teachers motivate students to learn by using various strategies, namely using various methods in the learning process, making students active participants, in motivating students to learn, namely internal factors, such as the students' motivation and desire to learn and external factors. , such as the ability of a reliable teacher.